Original paperDummy source digitization algorithm for reconstruction of flexible brachytherapy catheters with biplane images - Pálvölgyi, Jenö (Journal of Contemporary Brachytherapy, 2014)
Purpose: The traditional brachytherapy catheter reconstruction with biplane images is based on digitizing radio- opaque markers with a pointing device on a film or on a screen. An algorithm to automate digitization of radio-opaque marker coordinates on biplane images is presented. Material and methods: To obtain the marker coordinates in a proper sequence, instead of usual pair of reconstruction images, series of images were taken with insertion of radio-opaque markers consecutively into the catheters. The images were pre-processed to suppress the shield of anatomic structures. The determination of the marker coordinates is based on the detection of characteristic high gradient variation in pre-processed image profiles. The method was tested with six endometrial insertions performed with Simon-Norman catheters using our version of Heyman packing. Results: 28 catheters of six treatment fractions were digitized, typically 10 markers per catheter. To obtain the marker coordinates, adjustment of two threshold levels on the pre-processed images were needed. The coordinates of the radio-opaque markers on the biplane projection images were obtained without positive or negative artefact. Conclusions : The dummy source coordinates on the biplane images were digitized in a proper sequence: from the catheters’ tip towards the end of the catheters. After the three-dimensional reconstruction of the catheters from the digitized coordinates, the geometry file was imported by the brachytherapy planning system for dose calculation. The method has the advantage to eliminate manual digitization of the dummy sources.